2020
DOI: 10.15282/ijame.17.3.2020.06.0610
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis on Eco-friendly Machining of Ti6Al4V using Powder Mixed with Different Dielectrics in WEDM

Abstract: The recent scenario of modern manufacturing is tremendously improved in the sense of precision machining and abstaining from environmental pollution and hazard issues. In the present work, Ti6Al4V is machined through wire EDM (WEDM) process with powder mixed dielectric and analyzed the influence of input parameters and inherent hazard issues. WEDM has different parameters such as peak current, pulse on time, pulse off time, gap voltage, wire speed, wire tension and so on, as well as dielectrics with powder mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…One sample measurement of R a is illustrated in Supplemental Figure 1. Based on the past research work, 9,13,18,21,22 pilot experiments, and machine limitations, four parameters are considered for analyzing the responses such as MRR and SR in the present investigation. The selected input settings were T off , T on , I p , and PC, and their range was given in Supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One sample measurement of R a is illustrated in Supplemental Figure 1. Based on the past research work, 9,13,18,21,22 pilot experiments, and machine limitations, four parameters are considered for analyzing the responses such as MRR and SR in the present investigation. The selected input settings were T off , T on , I p , and PC, and their range was given in Supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Several dielectrics with suspended powder in the WEDM process also play an important role and provide better output. 18 Singh et al 19 explored the impact of tungsten powder mixed dielectric on EDM performance, such as MRR and machined surface characteristics. The result showed that a 48.43% improvement in MRR could be achieved in tungsten mixed kerosene.…”
Section: Introductionmentioning
confidence: 99%
“…However, molybdenum electrode wires have garnered comparatively lesser attention [23,24]. For the dielectric fluid media, oil and water are the key candidates, and water has been observed to be superior to oil in terms of its chemical stability and electrode wear rate [25]. In the present study, the electrode is made up of molybdenum and deionized water is used as the dielectric fluid.…”
Section: Introductionmentioning
confidence: 94%
“…Chakraborty et al [56] presented the performance of Ti-6Al-4V by mixing the powder in different dielectrics during WEDM. In the first stage, the experiment was conducted using a brass electrode of diameter 0.25 mm.…”
Section: Surface Integritymentioning
confidence: 99%